Methanol tolerant electrocatalysts for the oxygen reduction reaction - Asteazaran, Mariano (2014)
Direct methanol fuel cells (DMFCs) represent an interesting alternative in obtaining electricity in a clean and efficient way. Portable power sources are one of the most promising applications of passive DMFCs. One of the requirements in these devices is to use high alcohol concentration, which due to methanol crossover causes a considerable loss of fuel cell efficiency. In order to develop methanol tolerant cathodes with suitable activity, different supported catalysts namely PtCo/C and PtCoRu/C, were prepared either via ethylene glycol reduction (EG) with or without microwave heating assistance (MW) or via the alloy method, the latter followed by a thermal treatment in a reducing atmosphere (N2/H2). All cathode-catalysts were tested to determine the role of the components in simultaneously enhancing the oxygen reduction reaction (ORR) and discouraging the methanol oxidation reaction. According to the synthesis methodology, X-ray photoelectron spectra showed that the amount of metal oxides on the surface varies, being higher on the PtCo/C EG and PtCoRu/C EG catalysts. The electrochemical characterization of the catalysts was accomplished in a three electrodes electrochemical cell with a glassy carbon rotating disk electrode covered with a thin catalytic film as working electrode. To study the ORR and the influence of different methanol concentrations, linear sweep voltammetry and cyclic voltammetry were employed. The PtCo/C EG, with an important metal oxide amount on the surface, and the PtCoRu/C MW and EG electrodes, both with RuO2 on their surfaces, were the most tolerant to methanol presence.